Analisis Faktor-faktor yang Mempengaruhi Keberhasilan Turnaround pada Perusahaan yang Mengalami Financial Distress (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2014) - Sari, Puspa Novita, Imronudin, S.E, M.Si, Ph.D, Drs. M. Farid Wajdi, MM, Ph.D (2017)
This research aim is to analyze the influences of multiple organizational factors which are severity, firm size, free assets, assets retrenchment, dan cost retrenchment on turnaround outcomes of manufacturing companies listed in IndonesiaStock Exchange (BEI) from 2010 to 2014. Data used in this research are secondary ones which obtained from the Indonesian Capital Market Directory (ICMD) and the Indonesia Stock Exchange (BEI).The data are used as guidance to determine financial status calculated by Altman's Z-Score First Model (1986). The sample was selected using purposive sampling techniques, in order to obtain the sample accounted for 83 financial distress manufacturing companies which consists of 17 companies that managed the turnaround and 66 companies that failed turnaround. The results of the data analysis states that the accuration of model prediction is 86.7%, and there are 2 (two) variables that significantly influence the success of the turnaround companies experiencing financial distress that is Severity and Free Asset. Keywords: Turnaround, Financial Distress, Severity, Firm Size, Free Assets, Asset Retrenchment, Cost Retrenchment.